Role of Research in the Engineering Education - Devika, S. V.; Sarat Kumar, K.; SriKavya, K. Ch.; Patil, Swetha A. (Journal of Engineering Education Transformations, 2025)
The importance of research in Engineering Education has grown to levels of sophistication. Undergraduate research is a pedagogical tool that helps channelize the energy and enthusiasm of students into conceptual-based education, thereby igniting their minds to explore with curiosity of the world around them. The word "research" emits a groan from those who simply have no idea as to where to begin literally. This is a common response from most of us, especially in case of an engineering student. The fact is many of us procrastinate when it comes to doing research because we just don’t know how to do it. Although there is no quick fix when it comes to doing research, there are some practical approaches that make doing research a lot easier. The main objective to write this paper is to investigate students’ perception/attitude towards research. What are the techno factors that influence the cognizance.This paper focuses on the fundamentals of getting started with research, the students’ perception towards the research in their engineering education, the importance of its role in engineering education, the support of the students by the institution and as well as government carries out research activities in engineering education and the aspects to enhance engineering education without boundaries.